Increasing of Precision Technology of Glass Sorting Based on Very Fast Reconfigurable Image Processing - Krcmarik, David; Petru, Michal; Masin, Ivan (Manufacturing Technology Journal, 2019)
The paper deals with a method and technology for increasing of precision sorting of transparent materials - glass. The recycled glass is a valuable material which is necessary as an ingredient in the process of glass manufacturing. We propose a very fast industrial device based on FPGA (field-programmable gate array) image processing along with a novel algorithm for a robust real-time treatment of acquired data. The system consists from a line-scan camera with fast CameraLink interface, FPGA processing, battery of valves propelled via pneumatics and nozzle block. Very important part of the system is a background configuration software enables precise assessment of required limits as inputs to FPGA processing. The overall performance is discussed from the perspective of laboratory and industrial tests. The proposed FPGA image processing can be utilized for further future enhancements in the field of precise sorting of glass with stuck labels on it. The results give very good performance even in the industrial environment with a lot of dust and dirt and hence the glass does not need to be extensively cleaned.
Keywords: Glass cullet; sorting; optical processing; FPGA; color extraction; pneumatics